2015
DOI: 10.1371/journal.pone.0129173
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality Associated with Influenza among Tuberculosis Deaths in South Africa, 1999–2009

Abstract: BackgroundPublished data on the interaction between influenza and pulmonary tuberculosis (PTB) are limited. We aimed to estimate the influenza-associated mortality among individuals with PTB in South Africa from 1999–2009.MethodsWe modelled the excess influenza-associated mortality by applying Poisson regression models to monthly PTB and non-tuberculosis respiratory deaths, using laboratory-confirmed influenza as a covariate.ResultsPTB deaths increased each winter, coinciding with influenza virus circulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 29 publications
5
40
0
Order By: Relevance
“…In addition, HIV‐positive South Africans have been shown to be at greater risk for severe influenza illness 6. The high prevalence of underlying high‐risk medical conditions, including HIV and tuberculosis, likely contributes to higher influenza‐associated mortality in South Africa 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HIV‐positive South Africans have been shown to be at greater risk for severe influenza illness 6. The high prevalence of underlying high‐risk medical conditions, including HIV and tuberculosis, likely contributes to higher influenza‐associated mortality in South Africa 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…Another likely explanation for the trend toward higher female P&I mortality in the South involves the well‐known comorbidity of influenza and tuberculosis. Tuberculosis was highly prevalent in Newfoundland during this time period (House, ; Schmidt & Sattenspiel, ), and it has been repeatedly observed that infection with tuberculosis increases the risk of mortality from P&I (Mamelund, ; Noymer & Garenne, ; Oei & Nishiura, ; Walaza, Cohen, Nanoo, Cohen, McAnerney, von Mollendorf, Moyes, & Tempia, ). Preliminary observations of yearly vital records suggest that although tuberculosis had the highest mortality rates of any respiratory disease, year to year mortality rates did not vary significantly, and there was no clear significant excess during the 1918–1920 pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the influenza-associated mortality among individuals with PTB in South Africa from 1999-2009 observed an increased risk of influenza-associated mortality in persons with PTB compared to non-tuberculosis respiratory deaths [44]. In the same period of time (1999-2009), in South Africa, the mortality associated with seasonal and pandemic influenza among pregnant and non-pregnant women of childbearing age in a high HIV-prevalence setting was conducted.…”
Section: Mortalitymentioning
confidence: 99%